The Anatomy of Influence : Literature as a Way of Life - Bloom, Harold (New Haven ; London : Yale University Press, 2011)
Bloom leads readers through the labyrinthine paths which link the writers and critics who have informed and inspired him for so many years.
The point of view for my work as a critic. Literary love ; Sublime strangeness ; The influence of a mind on itself -- Shakespeare, the founder. Shakespeare's people ; The rival poet : King Lear ; Shakespeare's ellipsis : The tempest ; Possession in many modes : the sonnets ; Hamlet and the art of knowing ; Milton's Hamlet ; Joyce-- Dante-- Shakespeare-- Milton ; Dr. Johnson and critical influence -- The skeptical sublime. Anxieties of Epicurean influence : Dryden, Pater, Milton, Shelley, Tennyson, Whitman, Swinburne, Stevens ; Leopardi's Lucretian swerve ; Shelley's heirs : Browning and Yeats ; Whose condition of fire? : Merrill and Yeats -- Whitman and the death of Europe in the evening land. Emerson and a poetry yet to be written ; Whitman's tally ; Death and the poet : Whitmanian ebbings ; Notes toward a supreme fiction of the romantic self ; Near the quick : Lawrence and Whitman ; Hand of fire : Hart Crane's magnificence ; Whitman's prodigals : Ashbery, Ammons, Merwin, Strand, Charles Wright.
Includes bibliographical references and index.
Keywords: Bloom, Harold; Literature -- Appreciation; Literature -- Philosophy; Authors and readers; Influence (Literary, artistic, etc.)